Prevalence of Pathogenic Vibrio SPP and Molecular Characterisation of Selected Vibrio Cholerae Serovars Isolated from Seafood in Malaysia - Hussein Mohamed, Nasreldin Elhadi (2002)
The global resurgence of cholera is an important public health challenge as the number of countries affected by this infection continues to increase. Cholera continues to be a major health challenge in Malaysia. To adequately control the infection requires a thorough understanding of its modes of transmission and implementing a comprehensive programme which takes into account not only the health aspect but also social, economic, behavioral and political dimension as well. The food-borne cholera and other pathogenic vibrios have not been thoroughly investigated in food in Malaysia. This study demonstrated the presence of toxigenic and non-toxigenic Vibrio cholerae 01, Vibrio cholerae 0139, Vibrio cholerae non-0l/0139 and other vibrios pathogenic to mankind, which were isolated from seafood marketed from wet-markets and supermarkets from different locations in Malaysia from July 1998 to June 1999. In this prevalence study, a total of 768 seafood samples were examined for the presence of pathogenic Vibrio species. A total of 431 of 768 (56.1%) seafood samples were contaminated with Vibrios. The frequencies of Vibrio contamination in seafood were: shrimp (Panaeus indicus) 58.6%, squids (Logio sp.) 44%, squids (Sepia sp. ) 60%, cockles (Anadara granosa) 82%, blue crabs (Callinectes sapiduy) 62%, Shellfish (Lithophaga ma/accana) 48% and peel mussels (Perna viridis) 24%. V. damsela and V. alginolyticus was the most frequently isolated species, followed by V. meschnikovii, V. jluvalis, V. parahaemolyticus, V. vulnijicus, V. cholerae and V. mimicus. Of the 433 shrimp samples examined, 35.5% (254/433) were found to be positive for Vibrio, which yielded 791 isolates of Vibrios. Thus, 68.2 (58/85), 62.2 (28/45), 88 (22/25), 96 (24/25), 25 (5/20) and 100% (48/48) of the samples obtained from Selayang, Kajang, Bangi in Selangor; Seremban in Negri Sembi Ian; Penang (North Peninsula Malaysia); and Kuching in Sarawak (on Borneo island) yielded 158, 74, 62, 68, 14, and 231 isolates of Vibrios, respectively. Examination of 185 shrimp samples from Serdang wet market in Selangor over a nine-month period gave a contamination rate of 37.2% with incidence for the months ranged from 15 to 40%.